Materialism in Indian Thought - J B C (Journal of Dharma, 1976)
A characteristic note of contemporary Indian philosophical thought is the growing awareness that sufficient emphasis has not been placed in the past on matter and the material world, especially in view of the urgent need for material progress in the modern world. Kewal K. Mittal, in this book, explores the reasons for this neglect and tries to reconstruct the specific Indian type of ’materialism’ that was part of the various schools of the Indian tradition.